Zadanie
dodane przez
dynqa997
,
11.11.2012 09:53
a) - x(4x-1)
b) 2x + 3 - (4x+6)(2x - 3)
Nadesłane rozwiązania ( 2 )
Rozwiązanie 1
dodane przez
ALFA
,
11.11.2012 10:47
b) (2x+3)-(4x+6)(2x-3)=(2x+3)-2(2x+3)(2x-3)=(2x+3[1-2(2x-3)]=(2x+3)(1-4x+6)=(2x+3)(7-4x)=
=(2x+3)(7-4x)
-
- Dodaj komentarz
Musisz się
zalogować
aby dodać komentarz
Rozwiązanie 2
dodane przez
monijatcz
,
11.11.2012 11:06
a) -x(4x-1)= (4x-1)(4x-1)-x(4x-1)= (4x-1)[(4x-1)-x]=
= (4x-1)(4x-1-x) = (4x-1)(3x-1)
Musisz się
zalogować
aby dodać komentarz
COMMENT_CONTENT